Evaluation of the efficacy of low-level light therapy using 1072 nm infrared light for the treatment of herpes simplex labialis - Dougal, G.; Lee, S. Y. (Clinical and experimental dermatology, 2013)
Summary Background Recent research has shown that low‐level light therapy (LLLT) using 1072 nm infrared light is effective in reducing the duration of herpes simplex labialis (HSL) episodes and enhancing the healing process. Methods This was a prospective, randomized, placebo‐controlled, clinical trial to evaluate the efficacy of a 1072 nm light‐emitting diode device for the treatment of HSL. In total, 87 patients with recurrent HSL were recruited and randomly divided into two groups. Subjects received a 3‐min treatment with either 1072 nm infrared light therapy or placebo (sham) light therapy three times/day for 2 days. The devices used for both groups were identical in appearance and could not be differentiated by volunteers or researchers, and 1072 nm light is invisible to the human eye. The primary endpoint was healing time, which was taken as the time for the HSL lesions to resolve fully and for the underlying skin to become completely re‐epithelialized, and the secondary endpoint was lesion crusting. Results The median time to healing for the active group was 129 h, compared with 177 h for the control group, which was significant (P = 0.01). There was no difference between the two groups for median time to lesion crusting (P = 0.66). Conclusions Compared with placebo treatment, the treatment of HSL lesions with 1072 nm infrared light significantly reduced healing time.